The level of disclosure of financial and operational risks in commercial banks A study on the banking sector in Libya - العشيبي بدر الدين فرج; الوكيل نادية (Scientific Journal of University of Benghazi, 2023)
The study aims to identify the disclosure of financial and operational risks in Libyan commercial banks, and in order to achieve this, the researchers formulated an indicator to measure the level of disclosure through previous studies, and the study adopted the descriptive analysis approach. This study was applied to nine commercial banks in Libya, where the measurement period included a Four years from 2014 to 2017, through the method of content analysis of the annual reports published by banks, To achieve the objectives of the research, the level of risk disclosure was measured using an indicator to know the percentage of commitment to disclosure through Basel recommendations for measuring financial risks (return on equity - return on assets - liquidity risk - credit risk - capital adequacy risk) and also using the operational risk measurement indicator that was recommended It has Basel (basic indicator method - modular (normative) method - advanced standard method) and the ratio of Basel requirements (capital requirements - liquidity requirements - leverage ratio - future credit losses). The study concluded that the level of disclosure of financial and operational risks in the annual reports of commercial banks reached (5.51%), which is very weak, And that the banks did not address the directives and recommendations of Basel 2 or 3 in one of the pillars of Basel on disclosure and transparency, how to manage risks, and learn about methods of measuring them. The study recommended the need to expand the levels of disclosure of financial and operational risks in the annual reports, and that Basel requirements are receiving increased attention and awareness of their importance, and conducting more accounting research on the disclosure of financial and operational risks in the annual reports.